2012
DOI: 10.1111/j.2042-7158.2012.01589.x
|View full text |Cite
|
Sign up to set email alerts
|

Active halogen compounds and proteinaceous material: loss of activity of topical anti-infectives by halogen consumption

Abstract: The observed consumption effects are the result of the differing oxidizing (chlorinating) potencies. Since consumption and irritation are founded on the very same reactions, representatives with low reactivity (N-chloro amino acids) are regarded as more tolerable and retain more oxidative capacity, which provides a more sustained antimicrobial activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Under identical conditions (pH 7, 0·005 mol l −1 active halogen in the presence of 0·05% peptone), HOBr and the N ‐bromine derivatives of isocyanuric acid, and dimethylhydantoine lost 78–80% of the initial oxidation capacity within 1 h, while it was only 54–67% with the analogue N ‐chlorine compounds (Gottardi ). A further study using peptone and foetal calf serum revealed a throughout higher, but very similar consumption behaviour of the active bromine compounds compared to their chlorine analogues (Gottardi and Nagl ). The investigated N ‐chlorine compounds stood out by pronounced reactivity differences, which rank as HOCl > chloroisocyanuric acid > chloramine T > N ‐chlorotaurine, with HOCl showing a 3–4‐fold higher consumption than N ‐chlorotaurine (NCT; Gottardi and Nagl ).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Under identical conditions (pH 7, 0·005 mol l −1 active halogen in the presence of 0·05% peptone), HOBr and the N ‐bromine derivatives of isocyanuric acid, and dimethylhydantoine lost 78–80% of the initial oxidation capacity within 1 h, while it was only 54–67% with the analogue N ‐chlorine compounds (Gottardi ). A further study using peptone and foetal calf serum revealed a throughout higher, but very similar consumption behaviour of the active bromine compounds compared to their chlorine analogues (Gottardi and Nagl ). The investigated N ‐chlorine compounds stood out by pronounced reactivity differences, which rank as HOCl > chloroisocyanuric acid > chloramine T > N ‐chlorotaurine, with HOCl showing a 3–4‐fold higher consumption than N ‐chlorotaurine (NCT; Gottardi and Nagl ).…”
Section: Introductionmentioning
confidence: 87%
“…A further study using peptone and foetal calf serum revealed a throughout higher, but very similar consumption behaviour of the active bromine compounds compared to their chlorine analogues (Gottardi and Nagl ). The investigated N ‐chlorine compounds stood out by pronounced reactivity differences, which rank as HOCl > chloroisocyanuric acid > chloramine T > N ‐chlorotaurine, with HOCl showing a 3–4‐fold higher consumption than N ‐chlorotaurine (NCT; Gottardi and Nagl ). The N ‐bromine compounds, on the other hand, revealed a rather uniform reactivity.…”
Section: Introductionmentioning
confidence: 87%
“…However, the mild activity and high tolerability of N-chloro amino acids, particularly NCT, enable application of high concentrations to human tissue, which warrants a sufficient reserve of oxidation capacity despite some reduction (20). This can be of advantage compared with highly reactive oxidants that cause side effects at higher dosages (21).…”
Section: Discussionmentioning
confidence: 99%
“…An impressive example concerns NCT and the very reactive hypochlorous acid (HOCl). While the consumption of HOCl is twice as high (45), the bactericidal effect, however, is approximately 10,000-fold higher (51,67,68). This astonishing result can be reduced to both the faster penetration of HOCl and its superior oxidizing activity (see above), which causes immediate inactivation of S-H and S-CH 3 functions of vitally essential enzymes.…”
Section: Nonmicrobicidal Effects Caused By Chloramine Compoundsmentioning
confidence: 99%